Coexisting patterns and significance of serum HBV RNA and HBV DNA in patients with treatment-naïve chronic hepatitis B virus infection - Kun-yan Hao; Kun-yan Hao; Ye Fan; Yi-qing Zhang; Yue-cheng Yu (Frontiers in Medicine)
AimThe study aimed to explore the coexisting patterns and assess the significance of serum hepatitis B virus (HBV) RNA and traditional virological biomarkers in patients with antiviral treatment-naïve chronic hepatitis B virus (HBV) infection.MethodsSerum HBV RNA, HBV DNA, hepatitis B surface antigen (HBsAg), and hepatitis B envelope antigen (HBeAg) levels were measured and compared in patients with chronic hepatitis B virus infection. The HBV RNA levels were determined using a simultaneous amplification and testing assay.ResultsIn the HBeAg-negative (HBeAg [−]) patients, the serum HBV RNA detectable (HBV RNA [+]) rate (33.33%, 14/42) was significantly lower than the serum HBV DNA detectable (HBV DNA [+]) rate (95.24%, 40/42; p < 0.001). However, there was no significant difference in the HBeAg-positive (HBeAg [+]) patients (p > 0.05). The HBV RNA (+) rate (33.33%, 14/42) was lower in the HBeAg-negative patients than in the HBeAg-positive patients (100%, 17/17, p < 0.001), while the HBV DNA (+) rate (95.24%, 40/42 vs. 94.12%, 16/17) showed no significant difference (p > 0.05). The HBV RNA (+) rates showed a significant difference (p < 0.001) among the different HBsAg levels (10.00, 65.00, 84.21%, p < 0.001), while the HBV DNA (+) rate showed no significant difference (p > 0.05). In all patients, serum HBV RNA correlated well with HBV DNA (r = 0.72, p < 0.001), HBeAg (r = 0.68, p < 0.001), and HBsAg (r = 0.66, p < 0.001). However, the correlations between HBV RNA and other biomarkers varied across the different HBsAg and HBeAg levels.ConclusionThe coexisting patterns of serum HBV RNA and HBV DNA varied with the levels of HBeAg and HBsAg in the patients with treatment-naïve chronic HBV infection. This further suggests that serum HBV RNA should be included in the key index panel to accurately evaluate the natural history of HBV infection and the effects of antiviral treatment.